Speciálněpedagogická diagnostika surdopedická Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Doležalová, Lenka (Masaryk University Press, 2019)
Title in English: Special Needs Diagnostic - Hearing Disability: Methodical texts for the MUNI 4.0 project The text summarizes the fundamental features concerning the aetiology of hearing defects and the screening of children in an early, pre-school and school age. It introduces the service of the counselling institutions which represent the critical role in the specific period. These are early intervention and special needs centres which combine the domain of social and school care. The text includes an overview of diagnostic methods concerning the early age as well as the summary of the diagnostic process in children with hearing disability at pre-school and school age. Students would be able to study the examples of tests and materials applicated in practice with the focus on the organization and principles of the tasks. This material is aimed to create a successful combination with the lectures and discussions. The text is designed as a study and supportive material for the group and individual work. The following aim is to share the experience during the debates.